Feasible delivery system based on poly(lactictide-co-glycolide) nanoparticles loaded with antimicrobial mupirocin for possible wound healing - Košarišťanová, Ludmila; Komprda, Tomáš; Popelková, Vendula; Fialová, Tatiana; Vymazalová, Pavla; Astete, Carlos E (Acta veterinaria Brno, 2023)
The objective of the study was to assess cytotoxicity (based on the dimethylthiazol–diphenyltetrazolium bromide cell viability assay) and antimicrobial effects of poly(lactictide-co-glycolide) nanoparticles with entrapped mupirocin (PLGA/MUP NPs) on Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) strains using a disk-diffusion method, cryo-scanning electron microscopy (cryo-SEM) and fluorescence microscopy. Based on the evaluation of the growth curve, PLGA/MUP NPs inhibited growth of the both tested strains already at a concentration of 0.29 μg/ml, and their inhibitory effect at concentrations from 0.29 to 1.17 μg/ml was comparable with free MUP using the disk-diffusion method. PLGA/MUP NPs also tended to increase the abundance of the dead cells of MRSA, but not of S. aureus, in comparison with free MUP when evaluated by fluorescence microscopy. Further, cryo-SEM evaluation demonstrated an antibacterial-inhibitory effect of PLGA/MUP NPs on S. aureus in a dose-dependent manner. On the other hand, PLGA/MUP NPs cytotoxic activity tended to be substantially lower in comparison with both free MUP and empty PLGA NPs. It can be concluded that the excellent biocompatibility and satisfactory antibacterial effects of PLGA/MUP NPs constitute a suitable alternative as far as cutaneous wound healing is concerned.